On-farm evaluation of commercial feed and type of medication for weaned pigs - Pollmann, D.S.; Henry, Steven C.; Francis, E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A trial was conducted to evaluate the influence of diet composition and type of medication on pigs weaned at approximately 5 weeks of age (average initial weight of 15 pounds). A commercial feeding program containing extruded full fat soybeans was compared with a milo-soybean meal diet (19.2% protein and 1.25% lysine) containing neomycin (150 grams per ton) or neoterramycin (150 grams of neomycin and terramycin each per ton). Pigs were fed the treatments for 6 weeks while in the nursery. Performance was monitored continuously to market weight to evaluate the influence of the nursery treatments on the overall growth and carcass yield. The results of this study suggest that neoterramycin is superior (P<.05) to neomycin in starter pig diets. Pigs consuming the commercial feed had improved (P<.05) gain, feed efficiency, and number of days to market. But in this herd, the commercial feed increased mortality rate due to gut edema and increased feed cost per pound of gain (P<.05).
Keywords: Swine; Commercial feed; Medication; Weaned pigs